Determining conformational order and crystallinity in polycaprolactone via Raman spectroscopy. (19th May 2017) - Kotula, Anthony P.; Snyder, Chad R.; Migler, Kalman B.
Abstract: Raman spectroscopy is a popular method for non-invasive analysis of biomaterials containing polycaprolactone in applications such as tissue engineering and drug delivery. However there remain fundamental challenges in interpretation of such spectra in the context of existing dielectric spectroscopy and differential scanning calorimetry results in both the melt and semi-crystalline states. In this work, we develop a thermodynamically informed analysis method which utilizes basis spectra – ideal spectra of the polymer chain conformers comprising the measured Raman spectrum. In polycaprolactone we identify three basis spectra in the carbonyl region; measurement of their temperature dependence shows that one is linearly proportional to crystallinity, a second correlates with dipole-dipole interactions that are observed in dielectric spectroscopy and a third which correlates with amorphous chain behavior. For other spectral regions, e.g. C-COO stretch, a comparison of the basis spectra to those from density functional theory calculations in the all- trans configuration allows us to indicate whether sharp spectral peaks can be attributed to single chain modes in the all- trans state or to crystalline order. Our analysis method is general and should provide important insights to other polymeric materials. Graphical abstract: Highlights: The Raman spectrum of polycaprolactone is analyzed in both the semicrystalline and melt states. Single chain modes are separated from interchain modes. An interchain mode in the C=O stretch region provides a quantitative measure of crystallinity.